HEALTH SERVICES UTILIZATION OF REFERRAL HOSPITAL IN SIX LARGEST ISLANDS DURING THE COVID-19 PANDEMIC: EVIDENCE FROM INDONESIA (Proceedings of the International Conference on Public Health, 2022)
Background: Covid-19 pandemic caused changes in hospital utilization. Studies in several countries show decrease in hospital utilization. What about Indonesia, which has thousands of islands? There has been no research that can answer empirically. Purpose: This study aims to make comparative analysis of health services utilization before-after pandemic (2019-2020) in Indonesia's 6 largest islands: Sumatra, Java, Kalimantan, Sulawesi, Bali-Nusa Tenggara, Maluku-Papua. Method: This study is retrospective study. Data sources are taken from outpatient and inpatient claims for National Health Insurance Program (JKN Program). Comparisons are described by: hospital class (D-C-B-A), age group (ten years multiple), diagnosis and medical procedures. Result: Based on island, outpatient’s decreases range: 14%-31%, inpatient: 21%-34%. Outpatient’s highest decrease is in Maluku-Papua (-31%), and lowest is in Bali-Nusa Tenggara (-14%). Inpatient’s highest decrease happens in Sumatra and Sulawesi (-34%), while lowest is in Bali-Nusa Tenggara (-21%). Although Java is an island with largest population and Covid-19 cases, it does not show highest decrease. Each variable's decrease as follows: (a) outpatient: D hospital (-27%); 0-9 years old (-36%); Typhoid (-54%), dental procedures (-44%); (b) inpatient: C hospital (-32%); 10-19 years old (-38%); URTI (-54%), eye surgery (-36%). Conclusion: Outpatient’s highest decrease occurred in Maluku-Papua, while inpatient occurred in Sumatera and Sulawesi. Decreases occurred for young age group, bacterial infection diseases, also dental and eye procedures. While Bali-Nusa Tenggara were lowest decreases for outpatient and inpatient. Recommendation: This study recommends that authorities find out which health services are most needed during  pandemic in each island, develop teleconsulting policies to minimizing spread of Covid-19 and effective financing. Further research could be conducted on correlation between decline in utilization and number of Covid-19 in each island.
Keywords: Covid-19, health services, utilization, JKN Program